1994
DOI: 10.1002/ajmg.1320520110
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of body mass index in Williams‐Beuren syndrome

Abstract: Body mass index (BMI) is a useful tool for the investigation of obesity or underweight. It follows a typical pattern throughout childhood. During the first few years of life underweight due to feeding problems and gastrointestinal disturbances is considered a common sign in Williams-Beuren syndrome (WBS), whereas obesity is frequently reported in WBS adults. Systematic studies on weight gain and body mass index in WBS do not exist. Therefore, we studied weight gain relative to height expressed as BMI in 82 WBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…The deletion in this specific patient extended beyond D7S1870 to D7S489A polymorphic markers. Weight gain was observed in most cases after the age of 10, in contrast with the OFC and the height, which followed the anticipated growth parameters (23). It has been reported that the mean final height of girls and boys with WS is 153.9 Ϯ 6.9 cm and 168.2 Ϯ 6.9 cm, respectively (25).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The deletion in this specific patient extended beyond D7S1870 to D7S489A polymorphic markers. Weight gain was observed in most cases after the age of 10, in contrast with the OFC and the height, which followed the anticipated growth parameters (23). It has been reported that the mean final height of girls and boys with WS is 153.9 Ϯ 6.9 cm and 168.2 Ϯ 6.9 cm, respectively (25).…”
Section: Discussionmentioning
confidence: 80%
“…Recurrent vomiting as a result of gastroesophageal reflux, colic, and diarrhea is also common (23). GH deficiency has not been considered a major cause of growth retardation in WS, and in the literature, only one patient with confirmed GH deficiency responded well to therapy (24).…”
Section: Discussionmentioning
confidence: 99%
“…Age-related reference values for height, weight, and BMI were obtained from specific WBS charts [16][17][18] for WBS patients and from a wide sample of Italian children for healthy controls. 19 Height and BMI were normalised for chronological age by converting to SDS.…”
Section: Study and Laboratory Methodsmentioning
confidence: 99%
“…Weight was determined to the nearest 0.1 kg on a standard physician's beam scale, with the subject dressed only in light underwear and no shoes. Height, weight and pubertal stages were assessed according to international growth standards for WBS [16,17,18]. BMI was calculated and used as an indication of body fat mass.…”
Section: Methodsmentioning
confidence: 99%